(untitled) (Asian Education Studies, 2016)
Research presented here adopted a mixed method approach to data gathering in order to provide a case study that investigated reasons for students in a higher education context in Turkey failing the year due to repeated absenteeism. A survey administered to 109 students and 43 teachers revealed varying reasons and perceptions of why students were absent from language lessons. Individual and follow-up interviews with ten students revealed how absence was due largely to logistical and personal problems, principally commitment and motivation, rather than those related to learning or teaching, which reflects Longhurst (1999). Based upon these points, it is clear that in order to maximise language learning opportunities in the university preparatory year, the issue of both potential and actual students failing due to absenteeism (SFDA) requires urgent address.